Sustained Delivery of Ranitidine HCl from Floating Matrix Tablets: Formulation and in vitro Evaluation - Sahoo, B.K.; Gowda, K.V.; Mandal, U.; Das, A.; Chakrabarty, U.; Pal, T.K. (Asian Journal of Chemistry, 2010)
The objective of this study was the preparation of floating matrix tablets of ranitidine HCl, a novel H2-recepter antagonist used in ulcerative condition of upper part of gastro intestinal tract. Various formulations were prepared using rate controlling hydrophilic matrix materials (HPMC K100M), effervescent agents (sodium bicarbonate, citric acid) by the wet granulation method. The granules were evaluated for angle of repose, bulk density. The tablets were subjected to thickness, diameter, weight variation test, drug content, hardness, friability, lag floating time, total floating time and in vitro release studies. In vitro dissolution tests were performed in 0.1 N HCl for up to 12 h. The release kinetics of ranitidine HCl was evaluated using regression coefficient analysis. Among the prepared formulations, F7 & F8 showed satisfactory in vitro lag floating time as well as in vitro release in the initial hours and controlled release up to 12 h. FTIR and XRD studies further confirmed the integrity of the formulation. Most of the formulations exhibited diffusion dominated drug release. The results suggest that the floating matrix tablets could perform better than the conventional sustained release dosage forms, leading to improved efficacy and better patient compliance.